“I AM ALSO ALLOWED TO BE TIRED”: A CASE STUDY OF THE PERSON-CENTERED APPROACH IN THE FIRST DAUGHTER WHO FEELS BURDENED BY HER PARENTS' EXPECTATIONS - Elin Sagita Putri; Yasintha Sari Pratiwi (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to describe the psychological dynamics and changes in emotion regulation of a first-born adolescent girl who feels burdened by parental expectations through a Person-Centered approach. The research employed a qualitative single case study design. The participant was an eighth-grade female student experiencing pressure to remain strong and serve as a role model for her siblings. Data were collected through four individual counseling sessions using semi-structured interviews, observation, and anecdotal records, and analyzed using Miles and Huberman’s interactive model. Findings indicate that initially the participant suppressed her emotions to maintain a strong self-image. Throughout the counseling process, she gradually developed awareness of her emotional needs and shifted toward more open self-acceptance. The changes occurred gradually and remained influenced by ongoing family dynamics.